2012
DOI: 10.1542/peds.2012-0220
|View full text |Cite
|
Sign up to set email alerts
|

Acute Bacterial Osteoarticular Infections: Eight-Year Analysis of C-Reactive Protein for Oral Step-Down Therapy

Abstract: The combination of clinical findings and CRP is a useful tool to transition children with osteoarticular infections to oral therapy. Complicated outcomes were associated with higher early CRP at diagnosis and lower CRP at the end of parenteral therapy, suggesting that clinicians were more conservative with prolonged initial parenteral therapy in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 30 publications
1
49
0
5
Order By: Relevance
“…Las infecciones óseas y articulares por SARM-Co provocan elevaciones mayores en el nivel de PCR y la normalización es más tardía, lo que coincide con lo visto en esta serie 16 . El desbridamiento quirúrgico y el drenaje son la base del tratamiento de las infecciones osteo-articulares por SARM-Co y deben realizarse siempre que sea posible 16 .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Las infecciones óseas y articulares por SARM-Co provocan elevaciones mayores en el nivel de PCR y la normalización es más tardía, lo que coincide con lo visto en esta serie 16 . El desbridamiento quirúrgico y el drenaje son la base del tratamiento de las infecciones osteo-articulares por SARM-Co y deben realizarse siempre que sea posible 16 .…”
Section: Discussionunclassified
“…El desbridamiento quirúrgico y el drenaje son la base del tratamiento de las infecciones osteo-articulares por SARM-Co y deben realizarse siempre que sea posible 16 . La vía de administración óptima de los antimicrobianos no se ha establecido claramente.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…CRP, an acutephase reactant that is elevated during inflammatory processes and has a relatively short half-life, has been used to monitor patients' response to therapy. 9 Based on review of previous literature on the use of CRP as a marker, Davies et al 6 decided to start oral steroids for their patients when the CRP level decreased to <4 mg/dl.…”
Section: C-reactive Protein As a Marker For Initiating Steroid Treatmmentioning
confidence: 99%
“…Recently, Arnold et al reported 8 years' experience with a management algorithm to guide the transition to oral antibiotics in pediatric osteoarticular infections in a patient specific manner. 34 This study included 194 patients (154 uncomplicated and 40 complicated cases), all with culture-proven disease. Transition to oral antibiotics occurred based on resolution of fever and pain, improved function of the affected region, and a Creactive protein level of <3 mg/dL, and occurred at an average of 10 days into the treatment course.…”
Section: Acute Osteomyelitismentioning
confidence: 99%